2014
DOI: 10.1039/c4cc03851g
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput colorimetric assays for mercury(ii) in blood and wastewater based on the mercury-stimulated catalytic activity of small silver nanoparticles in a temperature-switchable gelatin matrix

Abstract: A catalysis-based, label-free, and high-throughput colorimetric protocol has been initially proposed for detecting mercury(II) in blood and wastewater with 96-cell plates, based on the mercury-enhanced catalytic activity of small silver nanoparticles synthesized in a gelatin matrix with unique temperature switchable sol-gel transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…The welldispersed lignin−AgNP complex solution with a concentration of 0.02 mg/mL was prepared, and different volumes (0, 50, 100, 150, 200, 250, 300, 350, 400, 450, and 500 μL) of Hg 2+ (HgCl 2 , 10 −3 mol/L) were added into 3 mL of lignin−AgNP solution. By contrast, 500 μL of many kinds of metal ions solutions (NaCl, KCl, CaCl 2 , Al(NO 3 2.5. Characterization of AgNPs and Lignin.…”
Section: Selective and Sensitivementioning
confidence: 99%
“…The welldispersed lignin−AgNP complex solution with a concentration of 0.02 mg/mL was prepared, and different volumes (0, 50, 100, 150, 200, 250, 300, 350, 400, 450, and 500 μL) of Hg 2+ (HgCl 2 , 10 −3 mol/L) were added into 3 mL of lignin−AgNP solution. By contrast, 500 μL of many kinds of metal ions solutions (NaCl, KCl, CaCl 2 , Al(NO 3 2.5. Characterization of AgNPs and Lignin.…”
Section: Selective and Sensitivementioning
confidence: 99%
“…9, 10 A variety of nanomaterials have been employed as colorimetric probes because of their unique physical and chemical properties. 11 Among those colorimetric probes, noble metal nanomaterials, especially gold nanoparticles (NPs), have been extensively used in nanoparticle aggregation-based colorimetric assays due to their high extinction coefficients and distance-dependent optical properties. 12, 13 However, gold NPs as colorimetric probes have to be confronted with some limitations for their wide application especially in resource-limited settings because of their intrinsic high cost.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Wang and co-workers found that small AgNPs showed relatively low catalytic activity in the 3,3,5,5-tetramethylbenzidine (TMB)À H 2 O 2 reaction at a low concentration. [26] However, when Hg 2 + ions were added into the reaction system, the catalytic activity could be significantly enhanced, which resulted in a visible deep blue reaction product. Based on the specific mercury-stimulated catalytic activity of AgNPs, they developed a colorimetric strategy for detecting Hg 2 + ions ( Figure 1D).…”
Section: Noble Metal Nanoparticles With Catalytic Behaviormentioning
confidence: 99%
“…D) Hg 2 + ion detection assay based on Ag nanoparticles. [26] Reproduced from ref. [26] with permission; copyright: 2014, Royal Society of Chemistry.…”
Section: Noble Metal Nanoparticles With Catalytic Behaviormentioning
confidence: 99%